Contribuição para diagnóstico e durabilidade de algumas edificações em estruturas de aço da cidade de Goiânia - Lima, Marcello Alencar (2015)
Recently have been noticed a few buildings made of steel structures in the city of Goiania, have shown process and progressive corrosion in your structural systems, and partly, for example, trusses, beams, columns etc. Such succession was visually perceived due to the aggressiveness of conditions relating primarily to the internal microenvironment of buildings, rain and animal feces. The methodology that was used is the data collection in the field of measuring thickness of the paint protection of apparent metal structures and photographic record of the problems of works, such as pathological manifestations of steel, paint, water accumulation sites etc. With the obtained data, the spreadsheet will be filled, depending on the model suggested by Mortari, 2008. In completing the Check list, it is easier to diagnose the structure, mainly because the diagnosis is last.